Impact of co-amoxicillin-resistant Escherichia coli and Pseudomonas aeruginosa on the rate of infectious complications in paediatric complicated appendicitis (Swiss Medical Weekly, 2019)
BACKGROUND Choice of antibiotics for complicated appendicitis should address local antibiotic resistance patterns. As our local data showed a less than 15% resistance of Escherichia coli to co-amoxicillin (amoxicillin + clavulanic acid), we opted for this antibiotic in 2013. Subsequently, the increasing prevalence of Pseudomonas aeruginosa challenged this choice. AIM OF THE STUDY The aim of this study was to describe the bacteriology of peritoneal swabs from cases of complicated appendicitis in our paediatric patients, and to determine the risk of infectious complications (wound and/or intra-abdominal abscesses). METHODS We designed a retrospective cohort study including all children (